2020
DOI: 10.1155/2020/8829587
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in a Patient with a Novel POU3F4 Mutation and Incomplete Partition Type-III Malformation

Abstract: Aims. This study is aimed at (1) analyzing the clinical manifestations and genetic features of a novel POU3F4 mutation in a nonsyndromic X-linked recessive hearing loss family and (2) reporting the outcomes of cochlear implantation in a patient with this mutation. Methods. A patient who was diagnosed as the IP-III malformation underwent cochlear implantation in our hospital. The genetic analysis was conducted in his family, including the whole-exome sequencing combined with Sanger sequencing and bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Either intraoperative CSF gushers during electrode insertion or an unexpected localization of the spiral ganglion neurons might hinder the CI outcome, even in a patient with a genotype allowing residual transcriptional performance. Chao et al [ 29 ] also reported an inconsistent distribution and responsiveness of the residual spiral ganglion neuron in IP type III, with CI outcomes varying accordingly. Furthermore, a recent study showed that POU3F4 variants were associated with neurodevelopmental disorders, such as hyperactivity, concentration difficulties, poor phonological working memory, and slow language development [ 22 ], all of which may contribute to a negative CI outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Either intraoperative CSF gushers during electrode insertion or an unexpected localization of the spiral ganglion neurons might hinder the CI outcome, even in a patient with a genotype allowing residual transcriptional performance. Chao et al [ 29 ] also reported an inconsistent distribution and responsiveness of the residual spiral ganglion neuron in IP type III, with CI outcomes varying accordingly. Furthermore, a recent study showed that POU3F4 variants were associated with neurodevelopmental disorders, such as hyperactivity, concentration difficulties, poor phonological working memory, and slow language development [ 22 ], all of which may contribute to a negative CI outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Smeds et al reported that very few DFNX2 children with cochlear implantation develop an age‐appropriate expressive language level and are rated to have adequate speech intellegibility 38,67 . Some studies also highlight the possibility that the benefits of implantation may decline over time (i.e., as the patient grows old) 11,14 . Choi et al 14 reported poorer auditory perception scores in DFNX2 patients 2 years after implantation relative to age‐matched cochlear implant recipients without inner ear malformations.…”
Section: Current Strategies To Treat Hearing Loss In Dfnx2 Patientsmentioning
confidence: 99%
“…It is supposed to be the least frequent among the incomplete partitions, accounting for 2% of them [45]. This anomaly causes a mixed hearing loss, frequently worsening over time, with initial benefit from a hearing aid, but eventually requires cochlear implantation [46].…”
Section: Incomplete Partition Typementioning
confidence: 99%
“…frequently worsening over time, with initial benefit from a hearing aid, but eventually requires cochlear implantation [46].…”
Section: Incomplete Partition Typementioning
confidence: 99%